The Death of Mr. Lazarescu - Puiu, Christus; Butică, Andrei; Mutu, Oleg; Fiscuteanu, Ion; Ana, Doru; Barladeanu, Monica (Tartan Video, 2006)
Two and a half hours of shaky handheld lensing about a man slowly expiring in a succession of hospitals becomes unexpectedly mesmerizing in helmer-scripter Cristi Puiu's sophomore Cannes entry "The Death of Mr. Lazarescu". Conceived as the first in a series titled "Six Stories from the Bucharest Suburbs", pic's dour take on the dehumanizing process of medical treatment is leavened by black humor and dialogue that always rings true. Running time will scare off customers, but hardy fest crowds should find the slog is worth moments of tedium. [www.variety.com]